Stroke rehabilitation at home before and after discharge reduced disability and improved quality of life: a randomised controlled trial. (March 2016) - Rasmussen, Rune Skovgaard; Østergaard, Ann; Kjær, Pia; Skerris, Anja; Skou, Christina; Christoffersen, Jane; Seest, Line Skou; Poulsen, Mai Bang; Rønholt, Finn; Overgaard, Karsten
Objective: To evaluate if home-based rehabilitation of inpatients improved outcome compared to standard care. Design: Interventional, randomised, safety/efficacy open-label trial. Setting: University hospital stroke unit in collaboration with three municipalities. Subjects: Seventy-one eligible stroke patients (41 women) with focal neurological deficits hospitalised in a stroke unit for more than three days and in need of rehabilitation. Interventions: Thirty-eight patients were randomised to home-based rehabilitation during hospitalization and for up to four weeks after discharge to replace part of usual treatment and rehabilitation services. Thirty-three control patients received treatment and rehabilitation following usual guidelines for the treatment of stroke patients. Main measures: Ninety days post-stroke the modified Rankin Scale score was the primary endpoint. Other outcome measures were the modified Barthel-100 Index, Motor Assessment Scale, CT-50 Cognitive Test, EuroQol-5D™, Body Mass Index and treatment-associated economy. Results: Thirty-one intervention and 30 control patients completed the study. Patients in the intervention group achieved better modified Rankin Scale score (Intervention median = 2, IQR = 2-3; Control median = 3, IQR = 2–4; P =0.04). EuroQol-5D™ quality of life median scores were improved in intervention patients (Intervention median = 0.77, IQR = 0.66–0.79; Control median = 0.66, IQR = 0.56 – 0.72; P =0.03). The total amount of home-based training in minutes highly correlated with mRS, Barthel, Motor Assessment Scale and EuroQol-5D™ scores ( P -values ranging from P <0.00001 to P =0.01). Economical estimations of intervention costs were lower than total costs of standard treatment. Conclusion: Early home-based rehabilitation reduced disability and increased quality of life. Compared to standard care, home-based stroke rehabilitation was more cost-effective.